Over-Dimension and Overloading Truck Accident Model with Structural Equation Modeling Partial Least Square - Ismatud Dianah Amir; Meriana Wahyu Nugroho; Tri Rijanto; Sumarsono Sumarsono (Buletin Profesi Insinyur, 2022)
Road accidents are an unavoidable problem, especially accidents caused by Over-dimension and Overloading trucks. This study involved environmental factors, driver factors, vehicle factors, and road factors which had previously been analyzed using the multinomial logistic regression method with questionnaire data of 194 respondents and resulted in 6 indicators including road surface conditions, traffic flow volume, accident history, vehicle load, vehicle dimension, and speed limit signs. The purpose of this study was to find out relationship between latent variables using the Structural Equation Modeling Partial Least Square (SEM PLS) method to obtain a model of the factors causing Over-dimension and Overloading truck accidents. The model results obtained indicate that weather conditions, road surface conditions, lighting condition, certified training, driver's physical condition, vehicle type, vehicle dimension, vehicle load, road geometry, accident location, traffic facilities, as well as vehicle dimension, and speed limit signs were the variables that had the greatest influence.The model obtained was good and fit (fit model) based on the  R2 and Chi-Square values of 65.7% and 76.3%, respectively.Keywords: Over-dimension and Overloading Trucks; Road Accidents; SEM PLS; Factors Causing Accidents